Montesquieu’s Classification of Law and The Genealogy of Peace - Baxshilloyevich, Sharipov (Indonesian Journal Publisher, 2025)
This article analyzes the views of the French philosopher Charles-Louis de Montesquieu on political power, law, and society. He considered laws as a product of human intellect and explained the connection between the state and society. Montesquieu took a critical approach to the concept of “paternal authority” and emphasized that political power is based on dynastic foundations. The article also examines Montesquieu’s perspectives on international law, political and civil rights, as well as the relationship between war and peace. His views on democracy and national values are also discussed. The methodology of this article employs legal and political analysis, historical-comparative methods, and legal philosophy. Montesquieu’s theories are examined in relation to modern governance, comparing his views with those of Locke, Hobbes, and Kant. A systematic approach assesses his perspectives on despotism, monarchy, and republicanism within contemporary constitutional systems.